1993
DOI: 10.1007/bf01552156
|View full text |Cite
|
Sign up to set email alerts
|

The importance of arthroscopy in sports injuries in children and adolescents

Abstract: Within a 3-year period (1985-1988), 60 children and adolescents with knee injuries sustained mainly while skiing or playing football (soccer) underwent clinical examination, X-radiography and arthroscopy. Nearly all the patients still had open epiphyseal plates in the knee region. Arthroscopy revealed more severe intra-articular trauma than had been suspected on the basis of clinical findings. The skiing injuries most commonly involved anterior cruciate ligament tears, whereas injuries of the patellar retinacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
9
0
5
Order By: Relevance
“…The apparent increase in the incidence of this injury has been attributed to an increased participation in sporting activities among the young, but the introduction of MRI and arthroscopy may partially account for the increased frequency of this diagnosis. 28,29 The conservative treatment of these injuries has been consistently associated with poor outcomes, including progressive instability, meniscal injuries and osteoarthrosis. Aichroth, Patel and Zorrilla 30 followed 23 patients managed conservatively for six years, by which time all had instability and ten had signs of arthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent increase in the incidence of this injury has been attributed to an increased participation in sporting activities among the young, but the introduction of MRI and arthroscopy may partially account for the increased frequency of this diagnosis. 28,29 The conservative treatment of these injuries has been consistently associated with poor outcomes, including progressive instability, meniscal injuries and osteoarthrosis. Aichroth, Patel and Zorrilla 30 followed 23 patients managed conservatively for six years, by which time all had instability and ten had signs of arthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion he difficulty in diagnosing pediatric and adolescent knee problems has been well documented [1][2][3][4][5][6][7][8][9][10] . Prior to the widespread access to and use of magnetic resonance imaging, knee arthroscopy had been advocated as a valuable diagnostic tool 9,[28][29][30] .…”
Section: Resultsmentioning
confidence: 99%
“…iagnosing knee disorders in children and adolescent patients can be difficult [1][2][3][4][5][6][7][8][9][10] . Harvell et al reported that a correct clinical diagnosis was made preoperatively in only 70% (141) of 202 knees in adolescent patients 5 .…”
mentioning
confidence: 99%
“…Über die in der Zeit von 1985-1988 erfaßten 60 Kniegelenkarthroskopien aufgrund von Verletzungen, die im Rahmen sportlicher Aktivitä-ten zustandegekommen waren, wurde schon an anderer Stelle berichtet [9].…”
Section: Patienten Und Auswertungunclassified
“…Die häufigste klinische Fehldiagnose betraf, wie auch in der Literatur hervorgehoben [9], die in 12 Fällen vermutete Innenmeniskusläsion, hinter …”
Section: Patienten Und Auswertungunclassified